Stability of the DSM-5 Section III Pathological Personality Traits and Their Longitudinal Associations With Psychosocial Functioning in Personality Disordered Individuals. - Wright, Aidan G. C.; Calabrese, William R.; Rudick, Monica M.; Yam, Wern How; Zelazny, Kerry; Williams, Trevor F.; Rotterman, Jane H.; Simms, Leonard J. (Journal of Abnormal Psychology, 2015)
This study was conducted to establish (a) the stability of the DSM-5 Section III personality disorder (PD) traits, (b) whether these traits predict future psychosocial functioning, and (c) whether changes in traits track with changes in psychosocial functioning across time. Ninety-three outpatients (61% female) diagnosed with at least 1 PD completed patient-report measures at 2 time-points (M time between assessments = 1.44 years), including the Personality Inventory for the DSM-5 and several measures of psychosocial functioning. Effect sizes of rank-order and mean-level change were calculated. In addition, Time 1 traits were used to predict functioning measures at Time 2. Finally, latent change score models were estimated for DSM-5 Section III traits and functioning measures, and correlations among latent change scores were calculated to establish the relationship between change in traits and functional outcomes. Findings demonstrated that the DSM-5 Section III traits were highly stable in terms of normative (i.e., mean-level) change and rank-order stability over the course of the study. Furthermore, traits prospectively predicted psychosocial functioning. However, at the individual level traits and functioning were not entirely static over the study, and change in individuals' functioning tracked with changes in trait levels. These findings demonstrate that the DSM-5 Section III traits are highly stable consistent with the definition of PD, prospectively predictive of psychosocial functioning, and are dynamically associated with functioning over time. This study provides important evidence in support of the DSM-5 Section III PD model.